Measuring Openness, Conflict, and Dependency: Validation of the Student–Teacher Relationship Scale among Indonesian Youth Learners - Fidrayani Fidrayani; Yenny Rahmawati; Dewi Salistina; Nuraida; Novita Ashari (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study aimed to adapt the Student–Teacher Relationship Scale into Indonesian and to examine its psychometric reliability in the Indonesian educational context. The research participants were Indonesian teachers working with youth learners, selected through purposive sampling based on their direct instructional involvement with students. The adaptation process employed a quantitative methodological approach and followed standard cross-cultural procedures, including forward translation, back-translation, expert judgment, and cultural refinement to ensure semantic and conceptual equivalence. Data were collected using STRS which measures three core dimensions of teacher–student relationships: openness, conflict, and dependency. Reliability analysis was conducted using Cronbach’s alpha to assess internal consistency. The results indicated that the Indonesian version of the instrument demonstrated high reliability, with a Cronbach’s alpha coefficient of 0.894, suggesting strong internal consistency across items. Minor linguistic adjustments were implemented to enhance cultural appropriateness without altering the theoretical constructs measured by the scale. To sum up, the findings indicate that the Indonesian adaptation of the Student–Teacher Relationship Scale is a reliable instrument for assessing teacher–student relationship quality in Indonesian educational settings. The adapted scale can be applied by researchers and educational practitioners to better understand relational dynamics that contribute to children’s school adjustment and to inform educational intervention.